PENGARUH KELENGKAPAN PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNG MAKAN POJOK SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Agustyono, Dandy Dwi Kurniawan; Karnadi, Karnadi; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of the study was to determine the Effect of Product Completeness, Service Quality and Price on Purchasing Decisions at Warung Makan Pojok Situbondo with Consumer Satisfaction as an Intervening Variable. The sampling technique used in this study was simple random sampling of 99 consumers. Data analysis and hypothesis testing in this study used Structural Equation Model – Partial Least Square (PLS-SEM)The test results show that Product completeness has a significant effect on Consumer Satisfaction, Service quality has a significant effect on Consumer Satisfaction, Price has a significant effect on Consumer Satisfaction, Product completeness has a significant effect on Purchasing decisions, Service quality does not have a significant effect on Purchasing decisions Price has a significant effect on Purchasing decisions, Consumer satisfaction has a significant effect on Purchasing decisions, Product completeness has a significant effect on Purchasing decisions through Consumer Satisfaction, Service quality has an insignificant effect on Purchasing decisions through Consumer Satisfaction, Price has a significant effect on Purchasing decisions through Consumer Satisfaction.